Utilizing Island Growth in Superlattice Buffers for the Realization of Thick GaN-on-Si(111) PIN-Structures for Power Electronics - Michler, Sondre; Thapa, Sarad; Besendörfer, Sven; Albrecht, Martin; Weingärtner, Roland; Meissner, Elke (physica status solidi (b), 2024)
In this study, the effect of implementing island growth in an AlN/Al0.1Ga0.9N superlattice on the structural properties of vertical GaN-on-Si(111) PIN-structures is investigated. It is demonstrated by scanning electron microscopy (SEM) and atomic force microscopy (AFM) that islands are formed on-top of V-pits present in the AlN nucleation layer and that the island coalescence height can be controlled by the growth temperature. Defect selective etching analyses confirm a noteworthy reduction in the threading dislocation density (TDD), which diminishes from 1.2 × 109 cm−2 ± 7.5 × 107 cm−2 to 8.5 × 108 cm−2 ± 7.3 ×107 cm−2 as the island coalescence height increases from ≈160 nm to ≈450 nm, achieved by increasing the growth temperature. Cross-sectional transmission electron microscopy (TEM) shows that island growth is particularly favorable for the reduction of a-type dislocations. As a consequence of the significant reduction of a-type dislocations in the buffer, stress relaxation during the GaN film growth is reduced, which is supported by in situ wafer curvature measurements and high-resolution X-ray diffraction (XRD). Owing to the optimized island growth conditions, thick and crack-free GaN layers on Si(111) substrates are obtained with an absolute wafer bow of <50 μm.
CRIS-Team Scopus Importer:2024-11-22
Keywords: dislocations; GaN-on-Si; island growth; metal organic chemical vapor deposition